A Bibliometric Analysis of Global Research for Mapping the Green Entrepreneurial Intentions - Zevender, Poy Saefullah; Ahman, Eeng; Mulyadi, Hari; Kurjono, Kurjono; Kusnendi, Kusnendi (FKIP Universitas Lampung, 2025)
Abstract: A Bibliometric Analysis of Global Research for Mapping the Green Entrepreneurial Intentions. The discussion is carried out through publication trends, influential authors, and thematic developments in the context of green entrepreneurial intention. This research aims to explain the increasing importance of environmental sustainability and the role of green entrepreneurship in overcoming social problems, combating climate change, and encouraging environmental conservation. Although interest in the topic of green entrepreneurial intention research is increasing, there is a need for a comprehensive understanding of the factors influencing green entrepreneurial intention, as well as the evolution of research in this area. We used bibliometric analysis methods to examine bibliographic information quantitatively, concentrating on collecting data from the Scopus database, covering the years 2000–2024. The analysis has revealed a significant increase in research on green entrepreneurial intention, especially post-COVID-19, indicating increased awareness of environmental sustainability. The study also highlights the most cited articles and their impact on the field, emphasizing the importance of green entrepreneurial orientation and green knowledge management in driving green innovation. Findings suggest that green entrepreneurial intentions are an important area of research that has implications for policy, education, and business practice, as well as contributing to global efforts toward sustainable development. The original value of the article comes from its systematic approach in analyzing the green entrepreneurial intention research landscape, providing theoretical understanding and practical guidance for research and applications in this field. Keywords: sustainable entrepreneurship, entrepreneurship education, bibliometric analysis, green entrepreneurial intention.